2020
DOI: 10.5430/jha.v9n4p10
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 a health reform catalyst? —Analyzing single-payer options in the U.S.: Considering economic values, recent proposals, and existing models from abroad

Abstract: The United States has continued to face severe health coverage and spending challenges that have been attributed to a fragmented multi-payer and fee-for-service delivery system which has become even more exposed by the COVID-19 pandemic. Legislators and healthcare professionals have tried to answer the challenges faced by the U.S. health system through the introduction of several state and federal proposals for a “Medicare-for-all” like system, which have failed to be adopted likely due to the lack of consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Fourth, the questions about COVID-19 status did not differentiate between those individuals who had symptoms versus a confirmed laboratory test, yet the construct of believing that one has had COVID-19 is clinically relevant. Finally, in this study, we could not compare the sample population to an international sample to analyze the effect of the prosperity of a country or differences in national health care insurance plans [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the questions about COVID-19 status did not differentiate between those individuals who had symptoms versus a confirmed laboratory test, yet the construct of believing that one has had COVID-19 is clinically relevant. Finally, in this study, we could not compare the sample population to an international sample to analyze the effect of the prosperity of a country or differences in national health care insurance plans [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the attention is focused on diagnosis and treatment of COVID-19, understanding EMS use during COVID-19 provides valuable insight concerning the role of prehospital emergency services at national and regional levels [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In addition to providing information that can support effective EMS during the current pandemic as infection rates rise and fall, data from this study may help future planning and preparedness initiatives to strategically optimize resources for future pandemics and or events that have the potential strain the capacity of the national EMS system, which could potentially delay or prevent necessary life-saving treatment and transport of the sick and injured to the hospital [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regions with previous experiences in infectious diseases (eg, severe acute respiratory syndrome) have invested in their public health care system’s reformation to efficiently handle the current outbreak [ 15 ]. Western societies (eg, the European Union and the United States) seem to lack this kind of planning [ 41 ]. In addition, recent studies showed that COVID-19 spread could be more rapid among more prosperous countries [ 15 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies showed that COVID-19 spread could be more rapid among more prosperous countries [ 15 , 42 ]. Countries need to organize their health systems [ 15 , 41 ], establishing effective infectious diseases and crisis management planning [ 43 ] (eg, enhance monitoring techniques and screening tools) to prevent virus spread in the community. Future longitudinal studies may be needed to better describe the relation of real-time mobility data with COVID-19 transmission.…”
Section: Discussionmentioning
confidence: 99%